A cognitive approach to literary character: Percival as individual and hero in Virginia Woolf’s "The Waves" - Balossi, Giuseppina (Status Quaestionis, 2018)
The understanding of literary character has been, since Aristotle, an issue of debate amongst different schools of thought which, in broad terms, have viewed characters in the novel either as representations of human beings, or as types such as the hero and the false hero, the protagonist and the antagonist, or as explicating a narrative function necessary to plot development. Modernist authors created characters that represent both individuals and heroic types: Leopold Bloom in Joyce’s Ulysses is an ordinary individual incarnating the failure of the Homeric hero. Also in Woolf’s The Waves, we encounter a character whose name is that of the heroic figure of the medieval chivalric romances: Percival, an entirely silent character in an otherwise extremely dialogical and “eyeless book” (i.e. without an ‘I’ narrator; Woolf 1925: 203), who is entirely other-presented by the six speaking characters across their lives. This article aims to suggest how through a cognitive stylistics approach our understanding of Percival arises on the one hand from our background knowledge of the classical/medieval hero, and on the other from the information derived from the six flawed Edwardian characters that construe him. The analysis of Percival carried out here demonstrates how through the six speakers’ indirect presentation our inferencing of this exceptional fictional character calls for a continual process of refreshment from the outset that contributes to forming a mental image of Percival as an individual and as the hero of The Waves. Keywords: indirect characterisation, cognitive linguistics, quantitative and qualitative methods, Virginia Woolf, The Waves.